A CORRELATIONAL STUDY ON THE TRANSLATION ABILITY AND WRITING SKILL AT UNIVERSITAS RIAU - Pasaribu, Judika; Eliwarti; M. Syarfi (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2021)
This research intends to find out whether or not there is a correlation between students’ translation and writing ability at the English Study Program of FKIP Universitas Riau. There were 40 students from 6A class chosen as samples. The instruments were translation and writing tests. The translation test aims to measure the ability of the students in translating an Indonesian-English text. The writing test aims to measure the students’ ability in writing a descriptive essay. The data were obtained by calculating the translation and writing test results. Based on the calculation, it was found that the students have good translation and writing ability. Besides, the value of the correlation coefficient obtained was 0.521 which means that there is a positive correlation between students’ translation and writing ability. The correlation is categorized as fair correlation since the value of the correlation coefficient obtained is 0.521 which is in the range of 0.400 - 0.599. Considering the fact that there is a correlation between students’ translation and writing ability, it is suggested that the students should also concern about and improve their translation ability because it will also improve their writing skill.